COMPARISM OF EULER-LAGRANGIAN AND FISCHER’S METHODS OF PREDICTING DISPERSION COEFFICIENT (Nigerian Journal of Technology, 2013)
This paper is aimed at comparing the prediction of dispersion coefficient of a natural stream using a new Euler-Lagrangian model, Fischer’s models and Levenspiel and smith equation. In order to achieve this, stream data were extracted from “American Stream Tracer Aanalysis on Humboldt River” and applied to the models. Results showed that slightly higher values of dispersion coefficients were obtained using the Euler-Lagrangian model than Fischer’s. The percentage difference ranges from 4.26% to 16.59%. The Levenspiel and smith approach predicted values 1 to 3 times larger than the new method. In addition to the available data from literature, limited field data collected from River Ebere in Enugu State, Nigeria were used in the analysis. The new approach is less labourious, more time saving and more economical.